Initiative‐Resistance and the Australian Party System. (21st April 2020) - Botterill, Linda Courtenay; Fenna, Alan
Abstract : In the first half of the twentieth century, writing about Australian political parties was strongly influenced by the novelty of government — and the policy agenda — being led by the political arm of organised labour. This was reflected in the tendency for commentators to treat Labor as the driving force in Australian politics and policy, and to see non‐Labor as playing a predominantly reactive and oppositional role. Following strong criticism, the "initiative‐resistance thesis", as this perspective was termed, lapsed. Here we revisit the concept, tracking its origins, use, and ultimate demise in the 1960s, and reconsider its validity and relevance, particularly in light of its affinity with the international literature on the "impact of parties". While initiative‐resistance was never a "thesis" as such, and critics have overstated the hold it enjoyed in early accounts, we argue that there is merit to a version reformulated in clear propositional terms. Critics may also have overstated its weaknesses. We illustrate this by focusing on one of the main original criticisms: the need to do justice to the separate identity of the National Party in understanding an essentially two‐party system.